DEVELOPING ENGLISH LISTENING MATERIAL FOR THE SEVENTH YEAR STUDENTS OF JUNIOR HIGH SCHOOL - Wijaya Mahardika, I Gusti Ngurah Agung (Institut Hindu Dharma Negeri Denpasar, 2018)
The aim of this research is to develop listening materials for teaching listening skill for class 7 of Junior High School based on the School Based Curriculum and the criteria of good listening material. In order to do so, the researcher firstly defines the characteristics of listening materials and activities that should be developed for teaching listening skill for class 7 of junior high school based on the School Based Curriculum and the criteria of good listening material.The final product of this research is a set of listening material which consist of, 1) 3 Student Books which contain the Listening Material for the students, based on their academic ability. Workbook A contains type A activities for slow students, Workbook B contains type B activities for normal students, and Workbook C contains type C material for smart students. 2) A Teacher Book which contains the same Listening Material as the students’ listening material, completed with Teaching aids and instructions to increase the usability of the material, and the transcript of the Listening Tapes. 3) The last product is the Listening Material in the form of Compact Disc (CD) containing the whole Listening Material and the soft copy of the Listening Transcript.